How do energy efficiency, technology, natural resources and globalization impact environmental sustainability? Fresh evidence from load capacity curve theory - Liu, Zhangfa; Mehmood, Usman; Nassani, Abdelmohsen A. (Frontiers in Environmental Science, 2024)
For sustainable development, the roles of energy efficiency and renewable energy is undeniable. We are passing through the era of globalization and economies are expanding their economic activities across borders. In this scenario, nations are striving for sustainable economic development without hurting the climatic conditions. Therefore, this study employs Bai and Carrion-i-Silvestre unit root test and Westerlund cointegration tests. The variables were found to have mix order of integration and Westerlund test shows cointegration in the panel data. The Method of Moments Quantile Regression (MMQR) is used to ascertain the effects of energy efficiency and economic, environmental, and globalization factors on the load capacity factor (LCF), a measure of environmental quality in G-20 countries. Key findings supporting the Load Capability Curve (LCC) theory show that while initial economic growth (GDP) has a negative impact (coefficient of -0.035 at the median quantile), advanced economic growth (GDP²) improves LCF (coefficient of 0.513 at the 90th quantile and 0.388 at the median). The median quantile coefficient of 0.055 indicates a positive association between the consumption of renewable energy and LCF. Natural resources exhibit a coefficient of 0.061 at the 90th quantile and 0.037 at the median. However, there are drawbacks to both financial globalization and contemporary environmental technology; their coefficients at the median quantile are -0.021 and -0.058, respectively. The work suggests targeted strategies, including more stringent environmental legislation, backing for renewable energy, sustainable resource management, advancements in environmental technologies, regulation of financial globalization, and bolstering of international cooperation.